2007
DOI: 10.1107/s1600536807045114
|View full text |Cite
|
Sign up to set email alerts
|

1,8-Bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene

Abstract: Key indicators: single-crystal X-ray study; T = 223 K; mean (C-C) = 0.003 Å; R factor = 0.028; wR factor = 0.075; data-to-parameter ratio = 13.1.The title compound, C 26 H 18 Cl 2 O 4 , has two 4-chlorobenzoyl groups that are in an anti orientation and are approximately parallel. The interplanar angle between the mean planes of the two benzene rings is 7.99 (8) . These 4-chlorobenzoyl groups are twisted away from the attached naphthalene ring. The two interplanar angles between the mean planes of the chlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Analogous aroylated unsymmetrical naphthalene compounds, for example, 1,8-bis(4-chlorobenzoyl)-2-hydroxy-7-methoxynaphthalene and 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene (Nakaema et al, 2007), have two aroyl groups at the 1,8positions of the naphthalene ring system. The two 4-chlorobenzoyl groups have the same orientation with respect to the naphthalene ring core in 1,8-bis(4-chlorobenzoyl)-2-hydroxy-7-methoxynaphthalene, while they are in opposite directions in 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene.…”
Section: Structural Commentarymentioning
confidence: 99%
“…Analogous aroylated unsymmetrical naphthalene compounds, for example, 1,8-bis(4-chlorobenzoyl)-2-hydroxy-7-methoxynaphthalene and 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene (Nakaema et al, 2007), have two aroyl groups at the 1,8positions of the naphthalene ring system. The two 4-chlorobenzoyl groups have the same orientation with respect to the naphthalene ring core in 1,8-bis(4-chlorobenzoyl)-2-hydroxy-7-methoxynaphthalene, while they are in opposite directions in 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene.…”
Section: Structural Commentarymentioning
confidence: 99%
“…Recently, the authors' group has revealed that diaroylation at 1,8-positions of 2,7-dimethoxynaphthalene smoothly proceeds [16,17]. According to X-ray crystal structural study, the obtained 1,8-diaroylnaphthalene has unique non-coplanar alignment of aromatic rings [18]. The curious reversible aroylation behavior of the naphthalene derivative [16] and chemospecific and regioselective ethereal alkyl-oxygen bond cleavage reaction of aroylated naphthalenes [19] can be explained on the basis of the structural features of the aroylated naphthalenes.…”
Section: Introductionmentioning
confidence: 99%
“…22 Synthetic methods and spectral data for the precursor, 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene, have been reported in literature. 11,12,20 Measurements 1 H NMR spectra were recorded on a JEOL JNM-AL300 spectrometer (300 MHz). Chemical shifts are expressed in ppm relative to internal standard of Me4Si (δ 0.00).…”
Section: Methodsmentioning
confidence: 99%
“…The authors' recent work has focused on peri-aroylnaphthalene compounds and the homologous/analogous substances. [11][12][13][14][15][16][17][18][19][20] According to the X-ray crystal structural analyses of ninety peri-aroylnaphthalene compounds, the two aroyl groups are non-coplanarly situated to the naphthalene ring and ordinary oriented in an opposite direction (anti-orientation). The molecular packing of peri-aroylnaphthalene compounds are mainly stabilized by cooperation of several kinds of weak non-covalent-bonding interactions, i.e., four kinds of nonclassical hydrogen bonds, (sp 2 )C-H···O=C hydrogen bond, (sp 3 )C-H···O=C hydrogen bond, (sp 3 )C-H···OR hydrogen bond, and C-H···π hydrogen-bonding interaction, and π···π stacking interaction are observed in decreasing order of frequency.…”
Section: Introductionmentioning
confidence: 99%